Documental linguistics and documental semiotics: Spanish journey - Martines, Alexandre Robson [UNESP]; Almeida, Carlos Candido de [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2022)
The purpose of this research is to analyze the epistemological process of Documental Linguistics, as well as Documental Semiotics in Spain. Added to this, he also wants to analyze the relationship of these disciplines with Documentation developed in Spain. Also, establish brief relationships with the theories that act as the basis of Documental Linguistics, in this case Structural Linguistics and Documental Semiotics, in turn, Semiotics. For that, a qualitative methodology, descriptive type, of exploratory character was applied. It is a theoretical-bibliographic approach, with a critical and reflective purpose about the disciplines of Documental Linguistics and Documental Semiotics, as well as about Structural Linguistics and Semiotics. Thus, there is a metalinguistic process in the procedures that involve the interpretation of information and its organization into concepts and the representation of the document, through a translation of concepts responsible for representing document information, as this information is produced in natural language, therefore translated, in metalinguistic procedures, into specialized documental language. Therefore, studies that explore Knowledge Organization and Documentation Science are aligned with the importance of language in the document processing process. Thus, Linguistics makes it possible to extract from the document information that is implied and inscribed in its dialogical aspects, in an intertextual perspective, the so-called documental sign, the same measure, Peircean Semiotics makes it possible to treat documental semiosis.
Keywords: Documentary Linguistics; Documentary Semiotics; Documentation Science; Spanish documentation